(untitled) (Acta Scientiarum. Human and Social Sciences, 2022)
This article addresses consumer desire formation in Portuguese young people in the age group 15 to 29 years. The article mainly sought to answer the following core question: What is the importance of digital influencers for consumer desire formation in the assessed young Portuguese individuals? Forty-six young individuals were heard in one-on-one semi-structured interviews and during focal groups. Friends, advertisements, and digital influencers were the primary source of consumer desire formation in this survey, with emphasis on digital influencers. These influencers and their standardized content are nowadays main references for young people, although the herein assessed population experiences the contradiction of knowing how their desires are formed and that they try to control them. On the one hand, this reality reflects a social integration process, and, on the other hand, it amplifies the semi-formation of these young individuals, who end up uncritically conforming to ‘the always equal’.